Training of Posyandu Cadres in Pre-Hospital Management of Fever in Toddlers - Maisyaroh, Arista; Widianto, Eko Prasetya; Kurnianto, Syaifuddin (Universitas Padjadjaran, 2024)
Parents' lack of knowledge in managing febrile seizures at home can increase the risk of complications such as Neurotransmitter damage and Epilepsy Damage from long-lasting attacks. The purpose of this community service is to improve the ability of cadres and parents in first aid for febrile seizures at home in toddlers. The training involved 40 posyandu cadres and parents, who measured the knowledge of febrile seizure management before the exercise was carried out. After providing training using simulations, measurements were carried out. The data were analyzed with the Wilcoxon Signed Rank Test, and the p-value < 0.001 were obtained so that there were differences before and after the training so that the simulation method effectively improved cadres' ability and parents' first aid for febrile seizures. This training can increase the knowledge of cadres and parents in first aid for febrile seizures at home, which can reduce complications due to febrile seizures in a toddler.Keywords: Febrile seizures, pre-hospital management, toddler